THE INFLUENCE OF FINANCIAL KNOWLEDGE ON FINANCIAL BEHAVIOR IN GENERATION Z WITH SELF-EFFICACY AND FINANCIAL ATTITUDE AS MEDIATORS - Hendra Raza; Suhendri; Ikhyanuddin; Rico Nur Ilham (PT. Radja Intercontinental Publishing, 2024)
This research aims to explore the influence of financial knowledge on financial behavior in Generation Z by considering the mediating role of self-efficacy and financial attitudes. Generation Z is a young generation who grew up in the era of digital technology and has a big influence on the future economy. Financial knowledge is an important key in understanding how Generation Z manages their own finances. The research results show that financial knowledge has no effect on financial behavior. In addition, self-efficacy and financial attitudes also positively mediate the relationship between financial knowledge and financial behavior, indicating that Generation Z who have high self-confidence in managing finances tend to have better financial behavior and emphasize the importance of positive attitudes towards finance in forming wise behavior in financial management